The influence of humidity on the deformation and fracture behaviour of PMMA - Hamouda, A.M.S. (Elsevier Science, 2002)
The effect of relative humidity on the tensile deformation and fracture of poly(methylmethacrylate) (PMMA) has been studied. Seven sets of samples were conditioned under different environment: as-received specimens; dry specimens (zero moisture content); outdoor exposed specimens; water saturated specimens; specimens conditioned at three different relative humidities (75.5, 85.1, and 94.6%) using saturated salt solutions (NaCl, KCl, and KNO3, respectively). The main objective of this study is to investigate the effects of sorbed water on tensile mechanical properties of PMMA. Properties investigated include development of crazing, tensile fracture stress, strain to fracture and fracture surface morphology.